If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + 5x = -2(x + 6) Reorder the terms: 23 + 5x = -2(6 + x) 23 + 5x = (6 * -2 + x * -2) 23 + 5x = (-12 + -2x) Solving 23 + 5x = -12 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 23 + 5x + 2x = -12 + -2x + 2x Combine like terms: 5x + 2x = 7x 23 + 7x = -12 + -2x + 2x Combine like terms: -2x + 2x = 0 23 + 7x = -12 + 0 23 + 7x = -12 Add '-23' to each side of the equation. 23 + -23 + 7x = -12 + -23 Combine like terms: 23 + -23 = 0 0 + 7x = -12 + -23 7x = -12 + -23 Combine like terms: -12 + -23 = -35 7x = -35 Divide each side by '7'. x = -5 Simplifying x = -5
| 7(1+8v)+2v=7-6v | | 6(1-2x)-5=-83 | | 24x^2+2xr-r^2=0 | | 2x^3+x^2-19x+36=y | | -[2]=x-9 | | -2(v+3)=-18 | | x^2+1.68=2.6x | | 5(-4+m)=-45 | | 2x^3+x^2-19x+36=x | | -5r-3=-33 | | 6(4x+7)=105 | | 5(n+5)=34+8n | | f(x)=2x^3+x^2-19x+36 | | 3(x+2.5)=-7.5 | | x+6-2x-4=0 | | 9+3(2x-6)=14 | | -54=9n | | 6n-12=150 | | 3(x+2.5)=7.5 | | 4+2(a+4)=-20 | | 9x-6=2x+8 | | 4x+2(3x-6)=4 | | y=-2x-17 | | 2y+3=31 | | a+3+20=-1+3a+4 | | -10x=5x-1 | | 3=3x+3 | | 4d=-2(33+d) | | 1=3x+3 | | -1=3x+3 | | 10(-2)=-20 | | -5=3x+3 |